Phylogenomics for Chagas Disease Vectors of the Rhodnius Genus (Hemiptera, Triatominae): What We Learn From Mito-Nuclear Conflicts and Recommendations - Filée, Jonathan; Merle, Marie; Bastide, Héloïse; Mougel, Florence; Bérenger, Jean-Michel; Folly-Ramos, Elaine; Almeida, Carlos Eduardo; Harry, Myriam (Frontiers in Ecology and Evolution, 2022)
We provide in this study a very large DNA dataset on Rhodnius species including 36 samples representing 16 valid species of the three Rhodnius groups, pictipes, prolixus and pallescens. Samples were sequenced at low-depth with whole-genome shotgun sequencing (Illumina technology). Using phylogenomics including 15 mitochondrial genes (13.3 kb), partial nuclear rDNA (5.2 kb) and 51 nuclear protein-coding genes (36.3 kb), we resolve sticking points in the Rhodnius phylogeny. At the species level, we confirmed the species-specific status of R. montenegrensis and R. marabaensis and we agree with the synonymy of R. taquarussuensis with R. neglectus. We also invite to revisit the species-specific status of R. milesi that is more likely R. nasutus. We proposed to define a robustus species complex that comprises the four close relative species: R. marabaensis, R. montenegrensis, R. prolixus and R. robustus. As Psammolestes tertius was included in the Rhodnius clade, we strongly recommend reclassifying this species as R. tertius. At the Rhodnius group level, molecular data consistently supports the clustering of the pictipes and pallescens groups, more related to each other than they are to the prolixus group. Moreover, comparing mitochondrial and nuclear tree topologies, our results demonstrated that various introgression events occurred in all the three Rhodnius groups, in laboratory strains but also in wild specimens. We demonstrated that introgressions occurred frequently in the prolixus group, involving the related species of the robustus complex but also the pairwise R. nasutus and R. neglectus. A genome wide analysis highlighted an introgression event in the pictipes group between R. stali and R. brethesi and suggested a complex gene flow between the three species of the pallescens group, R. colombiensis, R. pallescens and R. ecuadoriensis. The molecular data supports also a sylvatic distribution of R. prolixus in Brazil (Pará state) and the monophyly of R. robustus. As we detected extensive introgression events and selective pressure on mitochondrial genes, we strongly recommend performing separate mitochondrial and nuclear phylogenies and to take advantages of mito-nuclear conflicts in order to have a comprehensive evolutionary vision of this genus.